DNA Methylation-Related circRNA_0116449 Is Involved in Lipid Peroxidation in Traumatic Brain Injury - Zheng, Ping; Ren, Dabin; Yu, Cong; Zhang, Xiaoxue; Zhang, Yisong (Frontiers in Molecular Neuroscience, 2022)
Circular ribonucleic acid (circRNA) has a critical effect in central nervous diseases, however, the exact role of circRNAs in human traumatic brain injury (TBI) remains elusive. Epigenetic modifications, such as DNA methylation, can modify the mRNA level of genes without changing their related DNA sequence in response to brain insults. We hypothesized that DNA methylation-related circRNAs may be implicated in the mechanisms of TBI. The methylation-related circ_0116449 was identified from differential methylation positions and shown to reduce the neuronal loss and lipid markers. Mechanical study indicated that circ_0116449 functions as a miR-142-3p sponge and increases the expression of its target gene: NR1D2, together with NR1D1 and RORA to suppress lipid peroxidation both in vitro and in vivo. Our study suggests that DNA methylation-related circ_0116449 may be a novel target for regulating lipid metabolism in TBI.